The impact of the president on the formation and profile of governments in conditions of labile multi-parytyism: from pressure to persuation – comments on a century of experience in Finland - Grzybowski, Marian (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
Professor Tadeusz Szymczak, an eminent constitutionalist and “good spirit” of Almae Matris Lodziesis, is mostly associated with studies on federalism in European countries and the institution of the president. The centenary of His birth prompts us to trace the evolution of status and influence of the president on the functioning of European state systems and to reflect on the transformations in the president’s constitutional and political status and its functioning. In the circle of evolving European presidents, the president of Finland has been transformed worthy reflection. One of the areas of significant constitutional impact – after eighty years – was the change of the constitutional regulation (by replacing the Act of 1919 with a new constitution of 1999 and, in such frame especially, exercising the president’s powers to appoint the prime minister and the government, accepting his resignation and inspiring the reconstruction of the party or personal composition of the cabinet. The dimension of the anniversary make us pay attention to the period that coincides with the time that has elapsed since the Professor’s birthday, i.e. a full century.